Energy metabolism in relation to oxygen partial pressure in human skeletal muscle during exercise. - Bylund-Fellenius, A C (1981)
1. The intramuscular oxygen partial pressure (pO2) in human gastrocnemius muscle was monitored during exercise and compared with metabolite concentrations reflecting the energy and the redox state in the tissue. Ten normal subjects and ten patients with peripheral vascular occlusive disease were investigated. 2. In normal subjects the pO2 at the end of exercise was related to the intensity of the exercise, expressed as effect (J/s) per contraction. 3. In both patients and normal subject the pO2 was related to the [ATP]/[ADP] ratio, the [lactate/[pyruvate] ratio and the phosphocreatine concentration in the muscle tissue at rest and during exercise. 4. At each pO2 value, a lower [lactate/[pyruvate] ratio was found in the muscle tissue of the patients compared with that of normal subjects. This was interpreted as a beneficial effect of the higher oxidative-enzyme capacity in the muscle of the patients. 5. The results show the importance of pO2 for the regulation of the energy and the redox state of the tissue. During exercise the changes induced in pO2 and thus the energy state will stimulate the respiratory rate. This might be an important link in triggering the oxidative-enzyme capacity in response to physical training as well as in peripheral vascular occlusive disease.